Repaired or unrepaired capsulotomy after hip arthroscopy: a systematic review and meta-analysis of comparative studies. Issue 3 (May 2020) - Lin, Yipeng; Li, Tao; Deng, Xinghao; Huang, Xihao; Zhang, KaiBo; Li, Qi; Li, Jian; Fu, Weili
Purpose: To conduct a systematic review and meta-analysis comparing the surgical techniques, clinical outcomes, rates of revision and conversion to arthroplasty and complications between a repaired and unrepaired capsulotomy after hip arthroscopy. Methods: A search of the PubMed, Embase and Google Scholar databases was performed to identify comparative articles published prior to 10 July 2019 that reported the capsule management strategy and clinical outcomes after hip arthroscopy. A narrative analysis and meta-analysis were performed to integrate and compare the results of the 2 groups. Results: 12 comparative studies ( n = 1185 hips) with an average (methodological index for non-randomized studies) MINORS score of 17.45 ± 2.02 were identified for analysis, of which 5 were included in the meta-analysis. The pre- to postoperative improvements in the modified Harris Hip Score (mHHS), Hip Outcome Score–Sport-Specific Subscale (HOS-SS), and Hip Outcome Score–Activities of Daily Living (HOS-ADL) revealed no significant differences between the repaired and unrepaired groups ( p = 0.40, 0.26 and 0.61, respectively). The risk ratio of the revision rate for the 2 groups was 0.66 ( p = 0.21). Evaluation of the MRI scans and the rate of heterotopic ossification also showed no significant differences. The most preferred capsulotomy techniques were interportal and T-shape. No postoperative hip instability was reported in any of the 12 studies. Conclusion: The currently published evidence is still not strong enough to confirm the superiority of repairing the capsule after hip arthroscopy; hence, routine repair of the capsule during surgery cannot be suggested.